Validation of a virtual reality model for neuroanatomy learning: new approaches to teaching - Virto Farfan, Carlos Hesed (2025)
Objective: To validate a virtual reality (VR) model designed for neuroanatomy learning by evaluating its impact in terms of realism, usefulness, practicality, enjoyment, and recommendation. Materials and methods: A descriptive, instrument-validation study was conducted to assess the model through expert judgment in the field of neuroscience. Forty-two professionals in neurology, neurosurgery, and psychiatry participated in the study. The system was rated for realism, usefulness, practicality, enjoyment, and recommendation using a structured 13-item questionnaire based on a five-point Likert scale. The VR model, developed through advanced photogrammetry, enabled interactive manipulation of three-dimensional (3D) brain structures. Participants employed VR headsets and hand controllers to explore, in detail, the anatomical and functional relationships within the brain. Results: Participants reported high overall satisfaction with the system, emphasizing both the realism of the images (mean = 4.76, SD = 0.43) and the system’s usefulness in understanding complex 3D relationships (mean = 4.78, SD = 0.41). However, practicality received a slightly lower score (mean = 4.36, SD = 0.61), suggesting opportunities for improvement in the user interface. Enjoyment of the experience also received positive ratings (mean = 4.58, SD = 0.51). In addition, most professionals recommended integrating the system into medical education (mean = 4.64, SD = 0.48), highlighting its potential as a complementary tool to traditional teaching methods. Conclusions: The validated VR model proved to be a valuable tool for neuroanatomy learning, providing an immersive experience that facilitates the understanding of the complex spatial relationships within the brain. Although areas for improvement were identified, particularly regarding system practicality, the findings suggest that this technology has the potential to transform advanced medical education by offering a more engaging, practical, and effective approach. Further refinements in design could enhance its accessibility and acceptance, thereby solidifying its role in contemporary medical education.